Psychosocial stress and stroke risk: meta-analysis of observational studies - Khalifa, Mostafa A.; Alardhi, Albandari Sultan; Alharbi, Ghadah Faleh S.; Mousa M. Alzahrani, Abdulmajeed; Taqi, Batoul Ali; Alsalman, Falwah Sami; Basher G. Albalawi, Mohand; Alzahrani, Saleh Ahmed; Abul, Hessah Haji; Hassan, Hayat Safwat; Alqarni, Ashwaq Dhafer N.; Ahmed, Shaima ShamsEldeen KhalfAllah; et al. (Frontiers in Neurology, 2025)
BackgroundPsychological stress has been increasingly recognized as a potential risk factor for stroke, but the strength and consistency of this association remained uncertain. This systematic review and meta-analysis aims to determine the overall association between broad psychological stress and broad stroke risk.MethodologySystematic searches of PubMed, Scopus, Web of Science, and OVID databases from 1990 to March of 2025. These searches utilized a strategy combining subject headings and keywords related to psychosocial risk factors and stroke. Twenty-eight studies met inclusion criteria (23 prospective cohort and 5 case-control), comprising over 950,000 participants. We excluded studies involving participants with a history of depression. Stroke was broadly defined to include ischemic, hemorrhagic, subarachnoid, TIA, and unspecified subtypes.ResultsOur meta-analysis of 23 prospective cohort studies found that individuals exposed to psychological stress had a 46% higher risk of experiencing stroke (HR = 1.46; 95% CI: 1.29–1.66; P < 0.01). Initial analysis revealed substantial heterogeneity (I2 = 82%), which was significantly reduced to 39% (HR = 1.45; 95% CI: 1.32–1.59; P = 0.02) after a sensitivity analysis. Analysis of five case-control studies yielded a pooled odds ratio (OR) of 1.10 (95% CI: 1.01–1.20; P < 0.01), also indicating a modest but significant elevation in stroke risk; however, heterogeneity remained high (I2 = 92%). Sex-stratified analysis showed comparable increases in stroke risk for males (HR = 1.33; 95% CI: 1.19–1.49) and females (HR = 1.44; 95% CI: 1.07–1.95), with no statistically significant subgroup difference (P = 0.61).ConclusionPsychological stress is significantly associated with an increased risk of fatal stroke, though publication bias and study heterogeneity highlight the need for cautious interpretation. Further research should aim to address methodological variability and selective reporting to refine our understanding of this relationship.